Surgery for high-risk localized prostate cancer - Jan Schmitges; Quoc-Dien Trinh; Jochen Walz; Markus Graefen (Therapeutic Advances in Urology, 2011)
Treatment of men with high-risk prostate cancer (PCa) remains challenging for urologists. The complex natural history of high-risk PCa and the lack of specific and accurate definitions for high-risk disease impede treatment decision making. Historically, surgery in this patient group has been avoided based on the perception of ostensibly higher complication rates associated with inferior functional and oncological outcomes. To date, no randomized data comparing different therapy approaches have been made available. Several investigators have reported that continence rates in patients after radical prostatectomy (RP) for high-risk disease seem to be unaffected. Similarly, in a large proportion of these men, a nerve-sparing procedure can be performed without a significant negative impact on surgical margin rates and with comparable potency results. Moreover, extended pelvic lymph node dissection (EPLND) contributes to accurate pathological staging with a marginal effect on perioperative morbidity. With regards to the benefits of RP on local recurrence and cure rates, realistic expectations regarding the success of RP alone or in the context of a multimodal approach should be provided during patient counseling.